HIV/AIDS post‐exposure prophylaxis knowledge and uptake among health professionals in Africa: Systematic review and meta‐analysis. Issue 8 (30th March 2022) - Tekalign, Tiwabwork; Awoke, Nefsu; Eshetu, Kirubel; Gelaw Walle, Belete; Teshome Guta, Mistire
Abstract: Background: Healthcare workers in developing countries are at particularly increased risk of infections from blood‐borne pathogens because of the high prevalence of such pathogens in their communities as well as the lack of basic personal protective equipment, such as gloves, gowns and goggles. For those exposed healthcare workers, the immediate administration of antiretroviral drugs following exposure to potentially infected blood or other bodily fluids is essential in order to minimize the risk of acquiring HIV infection. This review is aimed at estimating the pooled prevalence of knowledge and uptake of post‐exposure prophylaxis among healthcare providers in Africa. Methods: We accessed PubMed, Science Direct, Google Scholar, SCOPUS, African Journals Online (AJOL), Journal Storage (JSTOR) and EMBASE. The search for unpublished studies included Google and institutional repositories were also used. This meta‐analysis follows the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. The quality of studies was assessed using the modified Newcastle‐Ottawa Scale (NOS). Meta‐analysis was carried out with a random‐effects method using STATA v.14 software. Results: Out of 654 692 studies retrieved, 37 studies from four African regions involving 6482 healthcare providers were included in this meta‐analysis. The overall estimated pooled uptake and knowledge of HIV/AIDS post‐exposure prophylaxis among healthcare providers in Africa using a random‐effects model were 40.09% (95% CI: 30.14–50.04) and 57.67% (95% CI: 44.32–71.01) respectively, whereas the highest uptake and knowledge were 45.48% (95% CI: 24.79–66.17) and 61.37% (95% CI: 46.39–76.36) in the southern and eastern regions, respectively. Conclusions: The results of this meta‐analysis indicated that the knowledge and uptake of post‐exposure prophylaxis, one of the best approaches to tackling HIV/AIDS transmission, are significantly low. Therefore, healthcare organizations should work on strategies to increase knowledge and uptake of post‐exposure prophylaxis among healthcare providers. Registration: Prospero (ID: CRD42021244003).